Effect of hit rate and cognitive style on Bayesian reasoning: evidence from eye movements - Yin, Lin; Shi, Zifu; Liu, Mei; Chen, Huohong (Frontiers in Psychology, 2025)
While psychological research has established both probability information and cognitive style as key factors in Bayesian reasoning, their interactive effects remain underexplored. We conducted an eye-tracking experiment with 52 undergraduates using EyeLink II to examine how hit rate variations and field dependence/independence influence reasoning patterns during classic Bayesian tasks. Results revealed significant hit rate × cognitive style interactions across multiple eye-tracking measures (total/average fixation durations, area-specific dwell time, fixation proportion). The attention prioritization followed the order: hit rate > false alarm rate > base rate, though base rate information retained measurable influence. High hit rates amplified field-dependent participants’ base rate neglect, while field-independent individuals maintained stable attention allocation across conditions. Field-independent reasoners demonstrated superior concentration and more efficient cognitive resource allocation, employing systematic information-processing strategies. These findings clarify the cognitive hierarchy of probability weighting in Bayesian reasoning while validating the critical moderating role of individual differences in information processing styles.